Estudo da capacidade de adensamento urbano do litoral Norte de Maceió, nos bairros de Jacarecica e Guaxuma. - Nascimento, Frederika Araújo do (2007)
The North Coast of Maceió has large areas of eco- systemic and land escape value. Currently the region is being often occupied by civil construction works. However, the developers of this sector are not concerned with the environmental questions, raising this way preoccupation and interest among scholars and researchers in finding solutions for the current and future problems of degradation. The neighborhoods of Jacarecica and Guaxuma, the object of this study, are inserted in this context because they are experiencing a period of crescent urban transformation. The various types of real estate may lead to local sustainability risk that has insufficient sanitary infrastructure to support the verticalization that is supposed to be installed. The increase in the urban exploration of intense concentration may harm the eco-balance as well as the local urban balance while the city of Maceió does not have urban policies addressed to protect this region, which in turn, is vulnerably exposed to degradation generated by the installations of the gated communities constructed by the sea side. In this context, this dissertation aims to study these neighborhoods, with the objective of analyzing the urban environmental quality vis a vis the process of accelerated and disorganized urban expansion. In order to do this, it was necessary to create the basis of the sustainability indicator, use-density and ground occupation, following the guidelines and norms offered by the Urban and Construction Code of Maceió, 2007 and the Master Plan of Maceió, 2005, creating a simulation of urbanization that enable the analysis of the demand estimates for water and sewage, that came out in this process of urban expansion. This way, some questions can be raised such as: quality of the urban environment and the forms of intervention compatible with the necessities of the region that enable appropriate investments to handle such infra-structure services, aiming the sustainable development of the region.